Penyuluhan Kesehatan dan Edukasi Hipertensi kepada Keluarga - Sultan Al Adami pradana; sukmara aji; Tiya Rizki Novianti; tiara cahaya; triman tresnawan (Yayasan Inspirasi El Burhani, 2021)
Introduction: Hypertension is a health problem in the world. Complications have a major impact on the quality of daily life, including in life. Maximizing blood pressure control has become a benchmark for improving overall health. In addition to pharmacological treatment, non-pharmacological treatment such as dietary regulation plays a very important role in controlling blood pressure. Many food constituents such as potassium, sodium, magnesium, and potassium have been thoroughly studied in recent times. Meanwhile, of all the nutrients it has been shown to clearly recommend it and some things remain and continue to be studied. Dietary modification is often debated with patients which can then provide considerable benefits for controlling blood pressure. Hypertension or high blood pressure is a scourge that continues to heat up and becomes a major problem and priority in this country and around the world, because in the long term chronic elevated blood pressure will increase the risk of cardiovascular and renovascular complications. and cerebrovascular. The analysis of Kearney et al, shows that this increase in the incidence of hypertension is not uncommon. Objective: The purpose of health promotion is to control, prevent, and treat hypertension as well as provide broad insight to families in the community about hypertension. Methods: The counseling method used is a direct approach method through education and interviews as well as screening a short video about hypertension. Result: Participants are able to answer all the questions that have been prepared by the counseling team. Conclusion: The conclusion from the counseling results ended well with evidence of increased knowledge of participants who were given counselling.